The Severity of Intracranial Hemorrhages Measured by Free Hemoglobin in the Brain Depends on the Anticoagulant Class: Experimental Data. (20th July 2017) - Ware, Kyle M.; Feinstein, Douglas L.; Rubinstein, Israel; Battula, Prudhvi; Otero, Jose; Hebert, Lee; Wang, Tzu-Fei; Ivanova, Alexandra; Chaudhary, Shweta; Hemminger, Jessica; Brodsky, Sergey V.
Abstract : Background and Purpose. Anticoagulant therapy is broadly used to prevent thromboembolic events. Intracranial hemorrhages are serious complications of anticoagulation, especially with warfarin. Direct oral anticoagulants reduce but do not eliminate the risk of intracranial hemorrhages. The aim of this study is to determine the degree of intracranial hemorrhage after application of anticoagulants without additional triggers. Methods. Rats were treated with different anticoagulant classes (vitamin K antagonists, heparin, direct thrombin inhibitor, and factor Xa inhibitor). Brain hemorrhages were assessed by the free hemoglobin concentration in the brain parenchyma. Results. Vitamin K antagonists (warfarin and brodifacoum) significantly increased free hemoglobin in the brain. Among direct oral anticoagulants, thrombin inhibitor dabigatran also significantly increased free hemoglobin in the brain, whereas treatment with factor Xa inhibitor rivaroxaban did not have significant effect on the free hemoglobin concentration. Conclusions . Our data indicates that the severity of brain hemorrhages depends on the anticoagulant class and it is more pronounced with vitamin K antagonists.